2014
DOI: 10.1210/jc.2014-1139
|View full text |Cite
|
Sign up to set email alerts
|

IGF1R Signaling Is Necessary for FSH-Induced Activation of AKT and Differentiation of Human Cumulus Granulosa Cells

Abstract: The cumulus cell response to FSH resembles the differentiation of preantral to preovulatory granulosa cells. This differentiation program requires IGF1R activity and subsequent AKT activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
86
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 43 publications
6
86
1
1
Order By: Relevance
“…The effect of IGFBP-4 on basal CYP19A1 mRNA abundance was statistically significant (P Ͻ .01) when control and IGFBP-4-treated groups were compared using a t test. These results suggest that IGF-2 actions are required for FSH-induced granulosa cell differentiation and for basal CYP19A1 expression and are in agreement with our previous findings demonstrating that IGF-1R activity is required for FSHinduced granulosa cell differentiation (7). In addition, because human granulosa cells produce only IGF-2, the results demonstrate that IGF-2 is a physiological activator of the IGF-1R in these cells.…”
Section: Igf-2 Is Essential For Fsh-induced Stimulation Of Cyp19a1 Ansupporting
confidence: 92%
See 4 more Smart Citations
“…The effect of IGFBP-4 on basal CYP19A1 mRNA abundance was statistically significant (P Ͻ .01) when control and IGFBP-4-treated groups were compared using a t test. These results suggest that IGF-2 actions are required for FSH-induced granulosa cell differentiation and for basal CYP19A1 expression and are in agreement with our previous findings demonstrating that IGF-1R activity is required for FSHinduced granulosa cell differentiation (7). In addition, because human granulosa cells produce only IGF-2, the results demonstrate that IGF-2 is a physiological activator of the IGF-1R in these cells.…”
Section: Igf-2 Is Essential For Fsh-induced Stimulation Of Cyp19a1 Ansupporting
confidence: 92%
“…We previously observed that cumulus cells express low levels of the preovulatory differentiation markers including aromatase (CYP19A1), P450 side chain cleavage (CYP11A1), LH/choriogonadotropin receptor, and steroidogenic acute regulator. In addition, we demonstrated that FSH stimulates the expression of these genes and estradiol synthesis (7). In this report, we show that IGF-2 and FSH synergize to promote the proliferation and the expression of differentiation markers in human cumulus cells and that IGF-2 is required for the stimulation of these cells by FSH.…”
mentioning
confidence: 52%
See 3 more Smart Citations